Mycophenolic acid formulations in adult renal transplantation – update on efficacy and tolerability - Déla Golshayan; M Pascual; Bruno Vogt (Dove Medical Press, 2009)
Déla Golshayan1,2, M Pascual2, Bruno Vogt11Service of Nephrology and Hypertension, 2Transplantation Centre and Transplantation Immunopathology Laboratory, Department of Medicine, Centre Hospitalier Universitaire Vaudois (CHUV), Lausanne University, 1011 Lausanne, SwitzerlandAbstract: The description more than 30 years ago of the role of de novo purine synthesis in T and B lymphocytes clonal proliferation opened the possibility for selective immunosuppression by targeting specific enzymatic pathways. Mycophenolic acid (MPA) blocks the key enzyme inosine monophosphate dehydrogenase and the production of guanosine nucleotides required for DNA synthesis. Two MPA formulations are currently used in clinical transplantation as part of the maintenance immunosuppressive regimen. Mycophenolate mofetil (MMF) was the first MPA agent to be approved for the prevention of acute rejection following renal transplantation, in combination with cyclosporine and steroids. Enteric-coated mycophenolate sodium (EC-MPS) is an alternative MPA formulation available in clinical transplantation. In this review, we will discuss the clinical trials that have evaluated the efficacy and safety of MPA in adult kidney transplantation for the prevention of acute rejection and their use in new combination regimens aiming at minimizing calcineurin inhibitor toxicity and chronic allograft nephropathy. We will also discuss MPA pharmacokinetics and the rationale for therapeutic drug monitoring in optimizing the balance between efficacy and safety in individual patients.Keywords: kidney transplantation, immunosuppression, mycophenolic acid, mycophenolate mofetil, enteric-coated mycophenolate sodium, acute rejection, chronic allograft nephropathy